Organizational innovation, technological innovation, and export performance: The effects of innovation radicalness and extensiveness. Issue 2 (April 2017) - Azar, Goudarz; Ciabuschi, Francesco
Highlights: We examine the relationships among innovation types and firm export performance. Organizational innovation enhances technological innovation. Only technological innovation extensiveness is beneficial for export performance. Organizational innovation has a direct and indirect effect on export performance. Abstract: This study focuses on the relevance of different types of innovation for firms' export performance. Despite ample research on the innovation–performance relationship, previous studies have mainly focused on technological innovations, leaving the effects of organizational innovations relatively unexplored. Hypotheses on the relationship between organizational and technological innovations and firm export performance are tested by structural equation modelling using data from 218 Swedish export ventures. The results indicate that organizational innovation enhances export performance both directly and indirectly by sustaining technological innovation. Moreover, by fine-graining our analysis of the mediating role of technological innovation, according to its radicalness and extensiveness, for organizational innovation, we show how the latter enhances both the radicalness and extensiveness of technological innovation although, notably, only extensiveness is actually beneficial for export performance. This study helps alleviate the scarcity of research examining the links among different types of innovation in relation to export performance and contributes to international business and marketing literature by generating new evidence regarding the mechanisms through which organizational and technological innovations may improve export performance.